Vinayaki - Temples of India Project Team (Jio Institute, 2024)
This is a rare image of Vinayaki, the feminine aspect (consort in some traditions) of Vinayaka or Ganesha. It is one of the several images, once contained in the lost temples of the hill, which were later affixed on the walls of the Bhairon shrine complex. Only a partial image is visible as the lower portion was subsumed by the stairways built next to it. Locals wrongly identify this image as Ardhanarishvara-Ganesha, which they believe to be a fusion of Shiva, Shakti and Ganesha. She is holding a cup in one of her hands, an attribute found in many of the Shaiva and Shakta images of the site and associated with tantric tradition. She is likely a tantric Shakti and suggests a syncretic fusion of the Ganapatya and Shakta traditions.